PENINGKATAN KETERAMPILAN MENGGUNAKANMC.OFFICEPADA PEGAWAI DESA BOLOPLERET, KEC. JUWIRING, KLATEN. - Sumedi P Nugraha (Asian Journal of Innovation and Entrepreneurship, 2013)
In the area of governance, especially the ability to apply computer microsoft officehas now become the most important things that can not be circumvented.The fact thateverything is now in need of a wide range of recording and certificates in various aspectsof governance that make employees work for the public service should be able to useMicrosoft Office in order to work faster, accurate and time saving. Based onobservations and interviews between the writer and village employees found that manyof the village officials are not adept at using computers, especially Microsoft Office. Itmakes some of the work they are supposed to be with the help of computers becomefaster it becomes increasingly slow, not to mention the average village officials areemployees of the older generation who in the days of ancient schools have not been sofamiliar with computers. Therefore, the authors then formulate a society serviceprograms to help employees learn microsoft office. This activity is packaged in a relaxedstyle to better suit the local people so that they do not hesitate if they wantto ask andconsult about the use of computers. This activity took place in the village offices with atotal training time is as much as 24 hours.Keywords:Services, Skills, Microsoft Office